De spreker als speler - Hamans, Camiel (Acta Neerlandica, 2024)
This contribution discusses three forms of conscious word formation in Dutch that show characteristics of word play: (pseudo) embellished clipping, blending and libfixing. Traditionally, these word formation processes are considered unpredictable and not systematic. Analysis of these processes shows that they are by no means chaotic, but that they follow fixed rules and systematics. According to this research, language play is not unfocused, but follows rules of which the language user is not aware. The forms of language play analyzed here can lead to language changes, which should consequently not be regarded as accidental.